PENGARUH LITERASI KEUANGAN TERHADAP PENGGUNAAN DIGITAL PAYMENT PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TEUKU UMAR - Khoirun Nisa Hsb; Andi St Hadijah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
The development of information technology has driven an increase in the use of digital payment systems across various groups, including college students. One of the factors presumed to influence digital payment usage is financial literacy. This study aims to analyze the influence of financial literacy on the use of digital payments among students of the Faculty of Economics and Business at Teuku Umar University. The research utilizes a quantitative approach with primary data obtained through questionnaire distribution, yielding 238 respondents. Data analysis was conducted using simple linear regression with SPSS testing. The results indicate that financial literacy has a positive and significant influence on digital payment usage, with a calculated t-value of 8.907, which is greater than the t-table value of 1.651, and a significance value of 0.000 (less than 0.05). The coefficient of determination ($R^2$) of 0.252 indicates that financial literacy accounts for 25.2% of the variation in digital payment usage, while the remaining percentage is influenced by other factors outside this study. This research concludes that the higher the level of students' financial literacy, the higher their tendency to utilize digital payment services effectively, safely, and sustainably.